Penyakit Tidak Menular Melalui GEMPITA : Gerakan Memanfaatkan Sampah Organik Untuk TOGA - Syahla Farida; Ai Kurniasih; Mutiya Rahmah; Marshanda Darianti; E. Wipa Wildatu Saniah; Rafi Ashari Nuryana; Lutfi Hilman Abdullah; Andy Muharry (Lembaga Pengembangan Kinerja Dosen, 2024)
Non-Communicable Diseases (NCDs) are a serious health challenge in Indonesia, especially in Setiajaya Village, where low public awareness of NCD risk factors makes the condition worse. This study aims to increase public knowledge and awareness regarding NCDs through the